Cost-effectiveness of long-acting progestogens versus the combined oral contraceptives pill for preventing recurrence of endometriosis-related pain following surgery: an economic evaluation alongside the PRE-EMPT trial - Tracy E Roberts; Mark Monahan; Lee Middleton; Siladitya Bhattacharya; Versha Cheed; Jane P Daniels; Kevin G Cooper; Melyda Melyda (BMJ Open)
Objectives To evaluate the cost-effectiveness of long-acting progestogens (LAP), including levonorgestrel-releasing intrauterine system (LNG-IUS) and depot-medroxyprogesterone acetate (DMPA), compared with the combined oral contraceptives pill (COCP) in preventing recurrence of endometriosis-related pain postsurgery.Design Within-trial economic evaluation alongside a multicentre, pragmatic, parallel-group, open-label, randomised controlled trial (Preventing Recurrence of Endometriosis by means of Long-Acting Progestogen Therapy trial).Setting Thirty-four UK hospitals recruiting participants from November 2015 to March 2019.Patients Four hundred and five women aged 16–45 years undergoing conservative endometriosis surgery.Interventions The ratio of 1:1 randomisation to receive LAPs (LNG-IUS or DMPA) or COCP.Main outcome measures The primary evaluation was a cost-utility analysis based on cost per quality-adjusted life-year (QALY) gained at 3 years. We adopted a UK National Health Service perspective. Secondary analyses in the form of cost-effectiveness analysis based on a range of outcomes were also undertaken.Results For the primary analysis, the COCP group incurred an additional cost of £533 (95% CI £52 to £983) per woman compared with LAPs. Treatment with COCP generated additional QALYs of 0.031 (95% CI −0.079 to 0.139) compared with the LAP group over 36-month follow-up. The incremental cost-effectiveness ratio for COCP compared with LAPs is therefore approximately £17 193 per QALY. The probabilistic sensitivity analysis suggested that there was a 54.7% probability that COCP would be cost-effective at the £20 000/QALY threshold. The secondary analyses revealed results more in favour of LAPs.Conclusion Although the COCP has a slightly higher probability of being cost-effective at £20 000/QALY threshold, there remains considerable uncertainty, with only marginal differences in outcomes between the two treatments. The lower rates of further surgery and second-line medical treatment for women allocated to LAPs may make this option preferable for some women.Trial registration number ISRCTN 97865475.